PEMBUATAN DAN KARAKTERISASI MODIFIKASI ASPAL PENETRASI 60-70 DENGAN KARET ALAM BANDAR BETSY - Siregar, Alkhafi Maas; Ritonga, Winsyahputra; Surahman, Dedi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This research aim to modify 60-70 penetration of bitumen with natural rubber (NR) and characterized the addition of NR. Samples for the physical properties requisite of asphalt was madeby using NR refluxed with xylene. Acrylate acid and benzoyl peroxidethen added as compatibilizer. NR used as much as 1 phr, 2 phr, 3 phr and 4 phr, asphalt 100 phr, acrylic acid0.25 phr and benzoyl peroxide 0.0045 phr. Each sample involved the requisite of theasphalt physical properties which consists of penetration, softening point, ductility, specific gravityand lose weighttest. After involving the asphalt physical properties, samples then made intospecimens with asphalt and aggregate mixture. The specimen is a mixture of aggregate with asphalt of 5%, 5.5% and 6%. Specimen strength was test by including density,stability and flow test. Specimen strength test have the maximum on density values about 2.355 g / cc to 6% bitumen content with addition of 2 phr of NR, on stabilityvalues about 1,679 kg to 5.5%bitumen content with addition of 1 phr of NR, and on flow values about 4.67 mm to 6 % bitumen content with addition of 1 phr of NR. Research result concluded that the asphalt can be modified with NR and the optimum asphalt strength obtained with the addition of 1 phr of NR. Keywords: Asphalt, Natural Rubber, Acrylic Acid, Benzoyl Peroxide.